Synthesis and Characterization Of C-Hexyl Calix[4]Resorcinarena from Resorcinol-Heptanal Condensation - Desi Suci Handayani; Zainal Arifin Almaqqomul Amin; Triana Kusumaningsih; Abu Masykur (ALCHEMY Jurnal Penelitian Kimia, 2014)
Synthesis of  C-hexyl  calix[4]resorcinarene  through condensation reaction between resorcinol  and  heptanal  with  HCl  catalyst  has  been  investigated.  Synthesis  conducted  by the ratio of resorcinol: heptanal (1:1) using reflux for 6 hours in ethanol. Structural  analysis of  the  product  was  done  by  FTIR  and 1 H-NMR  spectroscopy,  while  the  characterization was  done  by  determining  melting  point.  The  product  was  golden  brown  powder  with  a yield 99.43%  and  melting point more than 300 °C.  Structural analysis with FTIR and 1 HNMR  known  vibration  and  signals  characteristic  of  calix[4]resorcinarena  group, the vibrations of the CH  bridge. Vibration of CH bridge appearance at wave number 1445 cm-1 and 1456  cm-1, while signal of CH bridge appearance at chemical shifts from  4.17 to 4.21 ppm.